Intellectual Modal Towards Company Value: A Systematic Literature Review Study - Aaron Marcelino; Ivan Saputra; Viona Fitriani; Vonny Safira (Global Research on Economy, Business, Communication, and Information, 2025)
This study aims to gain a comprehensive understanding of the development of research related to intellectual capital and firm value, as well as future research opportunities. A Systematic Literature Review (SLR) using the PRISMA framework was conducted with Publish or Perish and Google Scholar to identify 18 relevant articles published between 2021 and 2023 that meet the inclusion criteria. The findings indicate a positive and significant influence of intellectual capital on firm value. Several studies also identify the mediating roles of profitability and financial performance in strengthening this relationship. However, there are some inconsistent findings in certain sectors, influenced by industry characteristics and different methods of measuring intellectual capital. This review provides academic contributions and practical insights for strategic management, particularly in strengthening theories and implementing intellectual asset management to enhance firm value. Additionally, these findings are expected to enrich the literature and serve as a foundation for further research on intellectual capital and firm value across various industry contexts.